Student difficulties in solving geometrical problems from matematization perspective - E Suaebah; M Mardiyana; D Retno (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This study aim is to describe student difficulties based on matematization perspective in solving geometry problems. This research uses descriptive qualitative method by using purposive sampling technique. To investigate and understand these difficulties, we used material test and interview by the 8th graders of Junior High School in Indonesia. Horizontal matematization refers to the activity to tranform into symbolic matematical problem, and vertical matematization refers to reorganize matematical system by using same appropriate rules. The results of this study show that difficulties horizontal matematization are transfering a real world problem to a matematical model, Schematizing, and visualizing a problem in shapes and dificulties vertical matematization are ajusting, combining, refining, and integrating models. This research is expected to give information about the importence of matematization as crucial process in learning and teaching of geometry.